2009
DOI: 10.1063/1.3063692
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of silicon nanowire by nonequilibrium molecular dynamics simulations

Abstract: The thermal conductivity of silicon nanowires was predicted using the nonequilibrium molecular dynamics method using the Stillinger-Weber potential model and the Nose-Hoover thermostat. The dependence of the thermal conductivity on the wire length, cross-sectional area, and temperature was investigated. The surface along the longitudinal direction was set as a free boundary with potential boundaries in the other directions. The cross-sectional areas of the nanowires ranged from about 5 to 19 nm 2 with lengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
77
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 13 publications
9
77
2
Order By: Relevance
“…1(a), is found to increase rapidly with nanowire length below ∼300 nm. This behavior is in agreement with the work of Wang et al 18 Thereafter, the thermal conductivity varies more slowly approaching asymptotically a constant value at lengths over 1200 nm. The slow increase above 300 nm implies that the NW is in the diffusive phonon transport regime.…”
Section: A Length Dependencesupporting
confidence: 81%
See 1 more Smart Citation
“…1(a), is found to increase rapidly with nanowire length below ∼300 nm. This behavior is in agreement with the work of Wang et al 18 Thereafter, the thermal conductivity varies more slowly approaching asymptotically a constant value at lengths over 1200 nm. The slow increase above 300 nm implies that the NW is in the diffusive phonon transport regime.…”
Section: A Length Dependencesupporting
confidence: 81%
“…Hence, the obtained values only apply to the case of cross section of 9 × 9 unit cells, i.e. 3.5 × 3.5 nm 2 with (110) surface structure and temperature of 300 K. Since our cross section and surface orientation of the pure Si NW is different from previous studies, [18][19][20] no exact comparison can be made. For consistency with previous studies, we run one more case of pure Si NW with an exact cross section of 4 × 4 × 302 unit cells and (100) surface structure.…”
Section: A Length Dependencementioning
confidence: 93%
“…Numerous studies can be found in the literature regarding the thermal conductivity of Si NWs [3,4,5,6,7]. The effects of different scattering mechanisms, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…(3) appears because a phonon travels on average half the distance between boundaries before being scattered. 23,24 It has been shown that this would be a good approximation for the Debye model at temperatures higher than 80 K for polycrystalline silicon. 25 The empirical parameters h f and h b define the probability of specular scattering at free surfaces and internal boundaries, respectively.…”
mentioning
confidence: 99%